(untitled) (Research, Society and Development, 2022)
Objective: to identify scientific evidence on neonatal transport in the emergency medical service Methods: integrative review carried out between December 2020 and March 2021 in five national and international databases, and descriptors: “neonatal transport”, “newborn” and “ambulance”. 198 researches were found, of which 12 constituted the final sample. The material was analyzed and organized using simple descriptive statistics. Results: The publications highlighted that the use of neonatal transport is complex and requires assistive technology and specific qualified care. Conclusion: It is necessary to develop strategies that broaden the perspectives of professionals in neonatal transport.